Social Worker training and management in professional practices - Rua Sanchez, Luis Efren (2023)
Work is a fundamental concept in social theory, which focuses on the role it plays in social and human development. Professional practices are significant in the formation of the professional in the social area. Therefore, it was proposed as an objective; to base the theories of social work and professional practices, in order to guide students in their activities in an intervention. The methodology of this research is descriptive and analytical approach to understand the background, skills and importance of social workers to the needs that arise in society. Likewise, it is inserted in the bibliographic documentary category and was carried out using computer equipment with Internet connection to access the relevant digitized documentation. The research highlights the role of the social worker as an agent of change in communities, enabling individuals to critically analyze their relationship with their environment, regardless of their social status. In addition, the study stresses the importance of equipping social workers with the knowledge and skills necessary to meet the professional demands and needs of the labor market